Strategi Pengelolaan dan Pengembangan Kawasan Hutan Mangrove di Dusun Tangkolak Timur Kabupaten Karawang - Mohamad Sam'un; Mohamad Rom Ali Fikri; Zeni Ayu Lestari; Triadi Triadi; Tasyah Dwi Rahmawat (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2022)
Mangrove forest management is not optimal and its economic use is still limited. Mangrove areas can have a positive impact on the economic development of coastal communities. This study aims to find a strategy for managing and developing mangrove forest areas in Tangkolak Timur Hamlet, Karawang. The research was conducted in Tangkolak Timur Hamlet, Sukakerta Village, Cilamaya Wetan District, Karawang Regency. It is a qualitative research supported by quantitative data with a case study approach. Data were obtained by in-depth interviews, participant observation, documentation review and Focus Group Discussion. This study aims (a). Identify the existing condition of the mangrove forest (b). Identification of the management and utilization of mangrove forests by the surrounding community (c). Conducting strategic analysis of mangrove forest area management and development. Strategy formulation is done by SWOT analysis. Based on the results of the study, it can be concluded that the main strategy is to make a comprehensive and integrated development plan/development and management of mangrove areas by involving various cross-sectors from government, private and community elements. Then followed by making work programs and proposals for the development of mangrove areas as well as conducting a development network system between the government, the private sector and the community.